PERSISTENCE IN PERFORMANCE FOR MUTUAL FUNDS IN PERIODS OF CRISIS - Theodoros KARGIDIS; Chris GROSE (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice)
The study investigates the persistence in performance for a sample of South European funds, domiciled in Portugal, Italy, Greece and Spain. Employing the Sharpe ratio, risk adjusted performance is measured in an attempt to judge the influence of the 2008 crisis and the current debt crisis on funds’ inclination to persist in their previous returns record. Examination period extends from January 2004 to December 2010 incorporating stages of relative stability in the stock and bond markets while also capturing the early stages of the eurozone crisis. We categorize funds as winners and losers in consecutive 6-monthly periods, thus being able to judge persistence in the short run, while our results suggest that the identification of winners and losers could enable us to investigate the possibility to gain investment advantages through this finding. Overall results suggest evidence of persistent results, whether positive or negative, both during the 2008 crisis and the current debt crisis, leading us to deduce that factors leading to performance persistence are not affected by market changes, since medium to long term persistence bypasses any temporary market mischief. This finding could be of use for fund managers aiming at establishing viable investment strategies, at their epicenter being the exploitation of such clues, suggesting persistence in returns. A fund of funds manager employing funds both in equities and fixed income could potentially choose to invest exclusively or more heavily in the winners of previous periods and avoid accordingly poor performers, thus achieving higher returns on average. For this purpose simple investment strategies are employed where we test the outcome of an investment strategy that would invest on fixed income securities by choosing those funds that were winners in the distribution of returns in the previous 6-monthly period, while disinvesting from poor performers and funds switching sides in performance persistence measurement in consecutive periods. The eurozone crisis makes more apparent the need to make use of such anomalies which could result in over performance relative to market benchmarks or reduction in overall losses during periods of unrest in fixed income markets like the one currently faced. Bond funds could also prove a valuable “helping hand” to portfolio managers when equity markets suffer, but that is not guaranteed by all funds under the same market conditions.